Bi-Center Problem in a Class of $Z_2$-Equivariant Quintic Vector Fields (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we study the center problem for $Z_2$-equivariant quintic vector fields. First of all, for convenience in analysis, the system is simplifiedby using some transformations. When the system has two nilpotent points at $(0, ±1)$ with multiplicity three, the first seven Lyapunov constants at the singular points are calculated by applying the inverse integrating factor method.Then, fifteen center conditions are obtained for the two nilpotent singularpoints of the system to be centers, and the sufficiency of the first seven centerconditions are proved. Finally, the first five Lyapunov constants are calculatedat the two nilpotent points $(0, ±1)$ with multiplicity five by using the methodof normal forms, and the center problem of this system is partially solved.